M24 Validation of the COPD assessment test (CAT) as an outcome measure in bronchiectasis. (12th November 2019) - Finch, S; Laska, IF; Fardon, TC; Chalmers, JD
Abstract : Introduction: Objective assessment of symptoms in bronchiectasis is important for both research and in clinical practice. While disease specific questionnaires exist they are not widely validated or have not been shown to be responsive to interventions. The COPD assessment tool (CAT) is a short, simple, symptoms assessment tool widely used in COPD. The items included in the CAT are not specific to COPD and also reflect the dominant symptoms of bronchiectasis. We therefore performed a study to validate the CAT as an outcome measure in bronchiectasis. Methods: The CAT questionnaire was administered to two cohorts of bronchiectasis patients along with other QOL questionnaires. Patients underwent comprehensive clinical assessment. One cohort had repeated questionnaires collected before and after treatment of acute exacerbations. We analysed convergent validity, repeatability and responsiveness of the score and calculated the minimum clinically important difference using a combination of distribution based and anchor based methods. Results: In both cohorts there were positive correlations between the CAT and the St. George's Respiratory Questionnaire (SGRQ) in both cohorts (r=0.90, p<0.0001 and r=0.87, p<0.0001). There was a clear inverse relationship between CAT and QOL-B RSS (r=0.75, p<0.0001) and LCQ total score (r=0.77, p<0.0001), (noting that lower scores on both scales indicate worse symptoms). Patients with more severe disease based on the bronchiectasis severity index (BSI) had significantly higher CAT scores, and CAT also correlated with FEV1 (% predicted) and 6 Minute Walk Distance (6MWD). CAT increased significantly at exacerbation and fell at recovery. The intraclass correlation coefficient for two measurements 4 weeks apart while clinically stable was 0.88 95% CI 0.73–0.95, p<0.0001. Estimates of the MCID varied from 3–4 for distribution based methods and 3–5 for anchor based methods. An MCID of 3 was most consistent. Discussion: This study demonstrates that the CAT is a valid, responsive symptom assessment tool in bronchiectasis. The MCID is estimated as 3 points.